Integration Islamic Social Finance and SDGs: Perspective Maqasid Sharia Based on Scientific Mapping - Fitri Ana Siregar (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to analyze research trends related to the integration of Islamic social finance and SDGs in the perspective of Maqasid Shariah, published through the Scopus database from 2017 to 2024. This study uses a quantitative research method with bibliometric analysis by using R-Packages software and the Biblioshiny Web Interface for data analysis and visualization. The keywords used are Islamic social finance or Islamic finance or social finance or Zakat or Waqf and Sustainable Development Goals or SDGs or Maqasid Shariah. Based on the search results, 164 scientific papers were obtained. The results of the study show that the theme of Islamic social finance and SDGs in the perspective of Maqasid Shariah is still interesting to study today, although it fluctuates every year. The ISRA International Journal of Islamic Finance, the journal with the most discussions on Islamic social finance and the SDGs, was the most frequently discussed journal in 2022. The most frequently selected research keywords for the integration of Islamic social finance and the SDGs were Islamic social finance, Waqf, sustainable development goals, and co-occurrence network. The keywords Islamic Social Finance are linked to the Sustainable Development Goals and Maqasid Sharia, explaining the interconnectedness of the three terms note. This research has strategic implications for the development of scientific literature in the field of Islamic social finance and its contribution to the SDGs through the Maqasid Syariah approach and provides new contributions in identifying trends, collaboration patterns, and also conceptual maps of research quantitatively and visually. Penelitian ini bertujuan untuk menganalisis tren penelitian terkait integrasi keuangan sosial Islam dan Tujuan Pembangunan Berkelanjutan (SDGs) dari perspektif Maqasid Syariah, yang dipublikasikan melalui basis data Scopus dari tahun 2017 hingga 2024. Penelitian ini menggunakan metode penelitian kuantitatif dengan analisis bibliometrik menggunakan perangkat lunak R-Packages dan antarmuka web Biblioshiny untuk analisis dan visualisasi data. Kata kunci yang digunakan adalah keuangan sosial Islam atau keuangan Islam atau keuangan sosial atau Zakat atau Waqf dan Tujuan Pembangunan Berkelanjutan (SDGs) atau Maqasid Syariah. Berdasarkan hasil pencarian, diperoleh 164 artikel ilmiah. Hasil penelitian menunjukkan bahwa tema keuangan sosial Islam dan SDGs dari perspektif Maqasid Syariah masih menarik untuk diteliti hingga saat ini, meskipun fluktuatif setiap tahun. Jurnal ISRA International Journal of Islamic Finance, yang paling banyak membahas keuangan sosial Islam dan SDGs, menjadi jurnal yang paling sering dibahas pada tahun 2022. Kata kunci penelitian yang paling sering dipilih untuk integrasi keuangan sosial Islam dan SDGs adalah keuangan sosial Islam, Waqf, tujuan pembangunan berkelanjutan, dan jaringan ko-munculan. Kata kunci keuangan sosial Islam terkait dengan Tujuan Pembangunan Berkelanjutan dan Maqasid Syariah, menjelaskan keterkaitan antara ketiga istilah tersebut. Penelitian ini memiliki implikasi strategis bagi pengembangan literatur ilmiah di bidang keuangan sosial Islam dan kontribusinya terhadap SDGs melalui pendekatan Maqasid Syariah, serta memberikan kontribusi baru dalam mengidentifikasi tren, pola kolaborasi, dan peta konseptual penelitian secara kuantitatif dan visual.